THE MAKING OF SYSTEM DATABASE USER FRIENDLY ON SMALL AND MEDIUM INDUSTRY (SMI) OF AUTOMOTIVE IN CENTRAL JAVA - Rusiyanto, Rusiyanto; Sumbodo, Wirawan; Kriswanto, Kriswanto (Universitas Negeri Semarang, 2015)
This paper about the making of system database user friendly on small and medium industry of automotive component in Central Java. The objective of this research is to make system data base with appearance user friendly and to know how high the level of customer’s satisfaction on the appearance of system database implemented on SMI automotive. This type of research is applied research, the research design uses evaluation research. This research result among others are resulted system database with appearance user friendly and the customer’s satisfaction level on appearance system data base is very high namely the average persentage is 97%.